Emotional competency and efficacy of teachers: Preschool education excellence indicator in Malaysia - Don, Yahya (UniversityPublications.net, 2014)
The purpose of this paper is to discuss emotional competency and self efficacy of preschool teachers as an important indicator of preschool educational excellence in Malaysia.This paper also discuss the difference between emotional competency and self efficacy of national preschool teachers and private preschool teachers in terms of demography factors (age, gender, teaching experience) and identify main dimensions in emotional competency that influence self efficacy of research respndents.The research implemented is in quantitative form, using cross-sectional survey approach to collect data related to current situation of emotional competency and self efficacy of research respondents.Research population involved national preschool teachers and private preschool teachers in the state of Kedah.Stratification random sampling technique was used to select sample from the research population.Research instrument used was Emotional Competence Inventory questionaire (ECI-2) (Boyatzis, 2001) and Teacher Self Efficacy (Mohd Zaaba Ismail and Zurida Ismail, 2002). Descriptive data analysis which involved respondent description such as frequency and percentage, Pearson correlation test, t Test, ANOVA and MANOVA.Research findings show that there is a positive and significant relationship between emotional competency of national preschool teachers and private preschool teachers and self efficacy. There is also a significant difference between age and teaching experience between national preschool teachers and private preschool teachers. Research outcomes show that emotional competency play an important role in improving self efficacy levels among preschool teachers in national schools and private schools.In view of that, the self awareness, social awareness, self management and relationship management groups should be considered as important elements in planning for programs to upgrade the level of skills and reinforcing teaching and learning qualities of national and private preschool teachers which directly contribute to raise the level of excellence on preschool education in Malaysia.